Krueppel-Like Factor 4 Expression in Phagocytes Regulates Early Inflammatory Response and Disease Severity in Pneumococcal Pneumonia - Herta, Toni; Bhattacharyya, Aritra; Rosolowski, Maciej; Conrad, Claudia; Gurtner, Corinne; Gruber, Achim D.; Ahnert, Peter; Gutbier, Birgitt; Frey, Doris; Suttorp, Norbert; Hippenstiel, Stefan; Zahlten, Janine (Frontiers in Immunology, 2021)
The transcription factor Krueppel-like factor (KLF) 4 fosters the pro-inflammatory immune response in macrophages and polymorphonuclear neutrophils (PMNs) when stimulated with Streptococcus pneumoniae, the main causative pathogen of community-acquired pneumonia (CAP). Here, we investigated the impact of KLF4 expression in myeloid cells such as macrophages and PMNs on inflammatory response and disease severity in a pneumococcal pneumonia mouse model and in patients admitted to hospital with CAP. We found that mice with a myeloid-specific knockout of KLF4 mount an insufficient early immune response with reduced levels of pro-inflammatory cytokines and increased levels of the anti-inflammatory cytokine interleukin (IL) 10 in bronchoalveolar lavage fluid and plasma and an impaired bacterial clearance from the lungs 24 hours after infection with S. pneumoniae. This results in higher rates of bacteremia, increased lung tissue damage, more severe symptoms of infection and reduced survival. Higher KLF4 gene expression levels in the peripheral blood of patients with CAP at hospital admission correlate with a favourable clinical presentation (lower sequential organ failure assessment (SOFA) score), lower serum levels of IL-10 at admission, shorter hospital stay and lower mortality or requirement of intensive care unit treatment within 28 days after admission. Thus, KLF4 in myeloid cells such as macrophages and PMNs is an important regulator of the early pro-inflammatory immune response and, therefore, a potentially interesting target for therapeutic interventions in pneumococcal pneumonia.